Development of higher order thinking skills module among preschool children: play - Anis Noratisha, Mohamad Isa (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The main aim of this research was to observe the technique used by preschool teacher in the development of Higher Order Thinking Skills (HOTS). To promote and understand HOTS, this research prepared a module for development of HOTS based on children interest. Basically, all the activities were prepared based on researcher observation during collecting data duration for about two weeks in Tabika Kemas and two days in Tadika Sri Mawar to test the module. The activities were originally from the kindergarten curriculum itself. The feedback from the children was measured by using emotional and social checklist either. The data was collected by using video recording to ensure no data missed. Besides, the module used Bloom Taxonomy three domains of learning which were affective, cognitive and psychomotor as an additional reference. In research involved two phases, which first phase was done at Tabika Kemas and second phases was done at Tadika Sri Mawar. This research was hopefully can give extra knowledge about the advantage of higher order thinking among parents and society.